Cases on establishing effective collaborations in academic libraries - Piorun, Mary E., 1969-; Raboin, Regina Fisher, 1956- (Hershey, PA : IGI Global, 2023)
'This book will identify and share the role of the academic library in developing effective partnerships and collaborations within academia and the broader community through a collection of case studies showing examples of successful collaborations, best practices, and innovative approaches to build and promote effective collaborations'--
Compilation of references : page 315-345.
Keywords: Academic libraries -- Relations with faculty and curriculum -- United States -- Case studies; Libraries and colleges -- United States -- Case studies; Library cooperation -- United States -- Case studies; Library outreach programs -- United States -- Case studies; Libraries and community -- United States -- Case studies